Advanced Technologies for the Optimization of Internal Combustion Engines - Tornatore, Cinzia; Marchitto, Luca (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue puts together recent findings in advanced technologies for the optimization of internal combustion engines in order to help the scientific community address the efforts towards the development of higher-power engines with lower fuel consumption and pollutant emissions.